Kebijakan Hukum Terhadap Pelaku Perundungan Di Sekolah Yang Berdampak Pada Perkembangan Mental Anak - Ardian Firmansyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The number of cases of criminal acts of bullying lately has increased, which is even sadder to the point where victims die. Of the several cases that have come to the public's attention is the bullying committed by children in the school environment. This phenomenon requires the government to issue policies to deal with cases of bullying. This research is intended to examine and provide an understanding of how legal policies are against perpetrators of bullying in schools and how big the impact of bullying is on the mental development of children as victims. This type of research is normative legal research with library research as the approach. The results of the study show that children as perpetrators of bullying should not be left alone in a peaceful settlement through the implementation of a diversion process outside the judiciary, but rather be given sanctions in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Article 82 paragraph (1) letter e of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, namely the obligation to attend formal education and/or training organized by the government or private bodies, is the proper legal basis for imposing sanctions on acts against children . In particular, some of the impacts of bullying on mental health are that the victim experiences trauma to the perpetrator, depression which causes the victim to experience a decrease in concentration, further loss of self-confidence, as a form of revenge, the victim has a feeling of wanting to bully, fear of being seen or noticed in public or social bullying , anxiety that tends to be excessive, dropping out of school and even the victim commits suicide. Meanwhile, the result of bullying for children's mental health is that victims of bullying tend to be alone because they feel the most guilty among others, victims have decreased self-confidence, reduced enthusiasm for life so they prefer to be moody and not anxious. For some people their emotions are getting more and more uncontrollable so that it results in a feeling of revenge in the victim's heart and makes them want to do what they have experienced against other people.